2021
DOI: 10.1007/s10640-021-00596-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Electric Vehicle Diffusion in China

Abstract: We analyze the effect of four determinants of electric vehicle diffusion in China for a panel of 31 regions for the period 2010–2016. We analyze diffusion of four different electric vehicle types, namely battery electric cars and buses as well as plug-in hybrid electric cars and buses. System GMM panel estimation results show that total monetary subsidies have a positive effect only on the diffusion of battery electric cars. A closer look reveals that subsidies provided by regional governments are decisive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…ε it is a random error term. The key advantage of this method is that with lagged variables as instruments, strictly exogenous instruments are not necessary (Bharati and Jia, 2018), and endogeneity issues can be tackled (Kalthaus and Sun, 2021). In particular, the endogeneity caused by bidirectional causality between explanatory variable and explained variable can be solved (Liu et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…ε it is a random error term. The key advantage of this method is that with lagged variables as instruments, strictly exogenous instruments are not necessary (Bharati and Jia, 2018), and endogeneity issues can be tackled (Kalthaus and Sun, 2021). In particular, the endogeneity caused by bidirectional causality between explanatory variable and explained variable can be solved (Liu et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Based on data at the county level in Virginia (US), Jia & Chen documented that the density of charging points is highly correlated with the number of BEV registration numbers [57]. The same result was found in China [65] and Sweden [66], in which the availability of public charging increases the actual adoption of BEVs. However, Mukherjee & Ryan reported that a long distance to the nearest public charging stations positively influences BEV adoption in Ireland, although the effect is quite small [32].…”
Section: Contextual Factorsmentioning
confidence: 83%
“…Kalthaus & Sun reported that a 1% raise in monetary subsidies could lead to a 0.5% increase in newly registered BEVs [65]. In addition, Narassimhan & Johnson reported that a 1% raise in tax incentives results in a 1.15% increase in BEV purchases [67].…”
Section: Monetary Incentive Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitating conditions are defined as users' perceptions that infrastructure is available to support the use of technology [15]. In the context of this study, the availability of charging infrastructure is of paramount importance for the acceptance of EVs [16]. Maintenance facilities and parking areas equipped with compatible charging points are also necessary for using EVs [13].…”
Section: Charging Point Networkmentioning
confidence: 99%